1986
DOI: 10.1177/001316448604600210
|View full text |Cite
|
Sign up to set email alerts
|

Person Fit in the Rasch Model

Abstract: The idea of whether a person's response pattern is "believable" given his estimated ability is one of the central issues in measurement. This article traces the development of this idea from Thurstone to Rasch. It also presents the rationale behind the development of person analysis in the Rasch model. Finally, it presents data based on simulated response patterns which provide insight into the power and Type I error rates of the Rasch unweighted total and between person fit statistics under a variety of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 19 publications
1
69
0
3
Order By: Relevance
“…If indeed they have (or at least some of them do) then one would expect, as suggested by Smith (1986) and Lamprianou (2005), that an individual with an aberrant response pattern may exhibit such behaviour in other testing situations too. This means that aberrance may be a stable characteristic of individuals.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…If indeed they have (or at least some of them do) then one would expect, as suggested by Smith (1986) and Lamprianou (2005), that an individual with an aberrant response pattern may exhibit such behaviour in other testing situations too. This means that aberrance may be a stable characteristic of individuals.…”
Section: Discussionmentioning
confidence: 93%
“…He attributed his findings to the fact that the test items were mainly multistep mathematical problems with partial credit awarding for partial success instead of the usual dichotomous items found in the literature and to the low status of the tests and the non-stressful administration procedure in the classroom setting. Smith (1986) and Lamprianou (2005) suggested that an individual with an aberrant response pattern may exhibit such response behaviour in other testing situations too, implying that misfit could be a stable characteristic of individuals.…”
Section: Panayides (2009) Investigated Possible Associations Of Misfimentioning
confidence: 99%
See 1 more Smart Citation
“…Some indices-as, for example, Yen's chi-square (Yen, 1981) or Bock's chi-square (Bock, 1972)-may be applied to any of the commonly used IRT models such as the one-, two-, or three-parameter logistic models (1PL, 2PL, 3PL, respectively); others, such as the Rasch model's item fit statistic (Smith, 1988;Smith & Wright, 1987), are modelspecific indices. These fit statistics are or are based on chi-square (the Rasch model's t statistics are transfo~a tions of chi-square) and differ from one another With respect to the number intervals and the computation of the predicted score.…”
mentioning
confidence: 99%
“…In the IRT context several person fit statistics have been proposed that can be used to detect individual item score patterns that do not fit the IRT model (Levine & Rubin, 1979;Wright & Stone, 1979;Tatsuoka, 1984;Smith, 1985Smith, , 1986Klauer & Rettig, 1990;Drasgow, Levine, & McLaughlin, 1991;Glas & Dagohoy, 2007). See Meijer and Sijtsma (2001) for a review.…”
Section: Introductionmentioning
confidence: 99%